Persecution in 1 Peter : differentiating and contextualizing early Christian suffering - Williams, Travis B. (Novum Testamentum, Supplements, 2012)
In Persecution in 1 Peter , Travis B. Williams offers a comprehensive and detailed socio-historical investigation into the nature of suffering in 1 Peter. While interpreters commonly portray the conflict situation addressed by the epistle as \'unofficial\' persecution consisting of discrimination and verbal abuse, Williams demonstrates the inadequacy of this modern consensus by situating the letter against the backdrop of conflict management in first-century CE Asia Minor. Drawing on a wide range of historical evidence and on modern social-psychological perspectives, this work reconstructs the conflict situation of the Anatolian audience and offers important insights regarding the legal culpability of Christians following the Neronian persecution, the roles of local and provincial authorities in the judicial process, and the variegated conflict experiences of different socio-economic groups within the Christian communities.